Peran Guru dalam Penanaman Nilai Bersyukur melalui Penerapan Metode Pembiasaan untuk Anak Usia Dini - Siti Roisah; Siti Muntomimah; Rina Wijayanti (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to gain an in-depth understanding of the role of teachers in instilling the value of gratitude in children aged 4–5 years through the application of the habituation method at TK Plus Wahidiyah Poncokusumo. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation. The research subjects included Group A teachers and the school principal. At the same time, observations focused on children’s behavior during habituation activities such as morning exercises, collective prayers, and the recitation of Asmaul Husna. Data analysis was conducted using the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing, and was complemented by triangulation to ensure data validity. The findings suggest that the teacher’s role, utilizing the habituation method, is effective in promoting the value of gratitude. This is evidenced by children’s emerging habits of appreciating what others give them and spontaneously expressing gratitude, such as saying “Alhamdulillah,” in their daily activities.